Risk of neoplastic progression in Barrett’s esophagus diagnosed as indefinite for dysplasia: a nationwide cohort study - Kestens, Christine; Leenders, Max; Offerhaus, G. Johan A.; van Baal, Jantine W. P. M.; Siersema, Peter D. (Endoscopy, 2015)
Background and study aims: A histological diagnosis of “indefinite for dysplasia” (IND) in Barrett’s esophagus is used when a diagnosis of genuine dysplasia is equivocal. The aim of the present study was to assess the risk of progression to high grade dysplasia (HGD) or esophageal adenocarcinoma (EAC) after a diagnosis of IND in a nationwide cohort of patients with Barrett’s esophagus.Patients and methods: Patients with a first diagnosis of IND in Barrett’s esophagus between 2002 and 2011 were selected from a nationwide registry of histopathology diagnoses in The Netherlands. Patients were followed up until treatment for HGD, detection of EAC, or date of last endoscopy contact with biopsy sampling. Results: In total, 1258 patients met the inclusion criteria, of whom 842 (66.9 %) underwent endoscopic follow-up. Patients were followed for a total of 2585 person-years (mean ± SD 3.01 ± 2.6). Median duration until first follow-up endoscopy was 1.2 years (interquartile range 0.3 – 1.8 years). The progression rate from IND to the combined end point of HGD or EAC was 2.0 (95 % confidence interval [CI] 1.5 – 2.6) per 100 person-years and progression to EAC was 1.2 (95 %CI 0.8 – 1.6). After excluding cases with HGD or EAC within 1 year after IND diagnosis (n = 16), the progression rates were 1.4 (95 %CI 1.0 – 1.9) and 0.8 (95 %CI 0.5 – 1.2) per 100 person-years for HGD or EAC and EAC, respectively. Conclusion: In this large, population-based, cohort of patients with Barrett’s esophagus, the incidence rate of HGD or EAC following a diagnosis of IND was 1.4 per 100 person-years. The results demonstrate the need for additional studies to select the subgroup of IND patients with an increased risk of neoplastic progression.